EARLY PREDICTORS OF PATHOLOGICAL JAUNDICE DUE TO ABO HEMOLYTIC DISEASE - DR. NAVEEN G. NADIG; DR. A.C. BASAVARAJ (International Journal of Pharma and Bio Sciences, 2013)
ABO hemolytic disease is the most common blood group incompatible hemolytic processes of the newborn period and is the major cause of neonatal jaundice attributed to maternal infant blood incompatibility. This was a prospective cohort study which included 50 consecutive term appropriate for gestational age babies with blood group either A, B or AB, born to O +ve mothers as the study group and another 25 consecutive term appropriate for gestational age babies with O+ve blood group born to mothers with O +ve blood group served as controls. Cord blood was used for estimation of bilirubun levels. Mean cord bilirubin was increased in infants with group A and group B born to group O mothers. Significant jaundice was more often seen when mother-infant pair had O and A combinations respectively. When significant jaundice was going to develop serum bilirubin at 12 hours only was quite high and it kept on increasing and all the cases in the study group had developed significant jaundice by 24 hours, though we estimated serum bilirubin level upto 48 hours.